PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP PRESTASI KERJA KARYAWAN PT GERSINDO MINANG PLANTATION (GMP) PASAMAN BARAT - Endang Tirtana Putra; Endarwita Endarwita; Eko Putra; Helvina Srinada (JURNAL ILMIAH EDUNOMIKA, 2022)
This study aims to determine and analyze the influence of leadership and organizational culture on employee performance at PT. Gersindo Minang Plantation. The population of this study were all office staff employees of PT. Gersindo Minang Plantation as many as 42 employees. For sampling, the census sampling technique was used, namely sampling which was carried out by taking all the population as samples. The number of samples in this study were 42 employees. The results of the study found that there was a positive and significant influence on the leadership variable on the work performance of PT. Gersindo Minang Plantation. The organizational culture variable has a positive and insignificant effect on the work performance of PT. Gersindo Minang Plantation. The variables of leadership and organizational culture have a positive and significant effect on the work performance of PT. Gersindo Minang Plantation. The coefficient of determination for the independent variable seen from the R square is 0.393. That is, the magnitude of the contribution of the influence of independent variables on the dependent variable is 39.3%. Keywords: leadership, organizational culture and employee performance